Antimicrobial Resistance Patterns and Dynamics of Extended-Spectrum β-Lactamase-Producing Uropathogenic Escherichia coli in Cusco, Peru - Steev Loyola; Fátima Concha-Velasco; Jimena Pino-Dueñas; Nancy Vasquez-Luna; Paola Juarez; Carlos Llanos; Guillermo Salvatierra; Jesus Tamariz; Andres G. Lescano (MDPI AG, 2021)
Urinary tract infections (UTIs) are a common human infection. Antibiotic resistance in extended-spectrum β-lactamase (ESBL)-producing uropathogenic E. coli (UPEC) is a major therapeutic challenge due to limited treatment alternatives. The aim was to characterize the antimicrobial resistance (AMR) and dynamics of ESBL-producing UPEC isolates from UTI cases seen at a local hospital in Cusco, Peru. Ninety-nine isolates from respective patients were characterized against 18 different antibiotics. Latent class analysis (LCA) was used to evaluate the dynamics across the study time according to resistance patterns. The median age of patients was 51 years old, and nearly half were women. ESBL-producing UPEC isolates were slightly more frequent in outpatient services than emergency rooms, and there were higher resistance rates in males compared to females. Half of the ESBL producers were resistant to aminoglycosides and nitrofurantoin. Cefoxitin and fosfomycin resistance was 29.3% and 14.1%, respectively. Resistance to carbapenems was not observed. All isolates were multidrug-resistant bacteria, and 16.2% (16/99) were also classified as extensively drug-resistant bacteria. The resistance patterns varied across the study time and differed regarding sex and healthcare service. The study revealed high levels of AMR to commonly used antimicrobials and a dynamic circulation of ESBL-producing UPEC isolates with varying resistance patterns.